Fast digestive, leucine‐rich, soluble milk proteins improve muscle protein anabolism, and mitochondrial function in undernourished old rats. Issue 11 (12th September 2017) - Salles, Jérôme; Chanet, Audrey; Berry, Alexandre; Giraudet, Christophe; Patrac, Véronique; Domingues‐Faria, Carla; Rocher, Christophe; Guillet, Christelle; Denis, Philippe; Pouyet, Corinne; Bonhomme, Cécile; Le Ruyet, Pascale; et al.
Abstract : Scope: One strategy to manage malnutrition in older patients is to increase protein and energy intake. Here, we evaluate the influence of protein quality during refeeding on improvement in muscle protein and energy metabolism. Methods and results: Twenty‐month‐old male rats ( n = 40) were fed 50% of their spontaneous intake for 12 weeks to induce malnutrition, then refed ad libitum with a standard diet enriched with casein or soluble milk proteins (22%) for 4 weeks. A 13C‐valine was infused to measure muscle protein synthesis and expression of MuRF1, and MAFbx was measured to evaluate muscle proteolysis. mTOR pathway activation and mitochondrial function were assessed in muscle. Malnutrition was associated with a decrease in body weight, fat mass, and lean mass, particularly muscle mass. Malnutrition decreased muscle mTOR pathway activation and protein FSR associated with increased MuRF1 mRNA levels, and decreased mitochondrial function. The refeeding period partially restored fat mass and lean mass. Unlike the casein diet, the soluble milk protein diet improved muscle protein metabolism and mitochondrial function in old malnourished rats. Conclusions: These results suggest that providing better‐quality proteins during refeeding may improve efficacy of renutrition in malnourished older patients. Abstract : Malnutrition accelerates the age‐related loss of muscle mass and function. One of the nutritional strategies to manage malnutrition in older patients is to increase protein and energy intake. It is found that soluble milk proteins improved body composition and protein metabolism and mitochondrial function in muscle in old malnourished rats. These results suggest that providing better quality proteins during refeeding may improve muscle renewal and efficacy of renutrition in malnourished older patients.